Rearrange the equation

Root((a^2)+(7)^2)=z^2

to make a the subject.

rearrange theeqaution s-y=(5+y)/s

to make y the subject

find if

root((a^2)+(b^2))=a+b

is true for all values of a and b or some values of a and b or no vvalues of a and b

Printable View

- July 6th 2012, 08:41 PMMagicalTransposing eqautions and identities and explaining
Rearrange the equation

Root((a^2)+(7)^2)=z^2

to make a the subject.

rearrange theeqaution s-y=(5+y)/s

to make y the subject

find if

root((a^2)+(b^2))=a+b

is true for all values of a and b or some values of a and b or no vvalues of a and b

- July 6th 2012, 11:12 PMbiffboyRe: Transposing eqautions and identities and explaining
2nd part. Multiply both sides by s getting s^2-sy=5+y Then s^2-5=y+sy

So s^2-5=y(1+s) and (s^2-5)/(1+s)=y